Organizational change strategies in the Arab region: A review of critical factors - Rees, Christopher J.; Althakhri, Rashid (Journal of Business Economics and Management, 2008)
This conceptual paper explores the subject of organizational change in the Arab region with particular reference to cultural influences on organizational change initiatives in this region. The paper offers a review of a set of studies which focus on organizational change in Arab countries and proceeds to discuss change initiatives with reference to factors such as Islam and tribalism. A key issue that emerges from the paper is the paradox between Western approaches to change which emphasize collaborative and participative approaches to change management, and the more directive and hierarchical approaches to management associated with national cultures in the Arab region. Areas for future research are identified in the conclusion section. First published online: 14 Oct 2010